2016
DOI: 10.1152/ajpgi.00210.2015
|View full text |Cite
|
Sign up to set email alerts
|

Lactobacillus acidophilusstimulates intestinal P-glycoprotein expression via a c-Fos/c-Jun-dependent mechanism in intestinal epithelial cells

Abstract: Priyamvada S, Anbazhagan AN, Kumar A, Soni V, Alrefai WA, Gill RK, Dudeja PK, Saksena S. Lactobacillus acidophilus stimulates intestinal P-glycoprotein expression via a c-Fos/c-Jundependent mechanism in intestinal epithelial cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 57 publications
0
17
0
Order By: Relevance
“…However, the molecular mechanisms involved in the transcriptional modulation of HDPs are not well-understood. The AP-1 transcription factor complex is the main transcription factor downstream of MAPK pathways and can bind with specific DNA sequences (45, 46). In the present study, the AP-1 subunits c-fos and c-jun were activated in IPEC-J2 cells incubated with L. plantarum ZLP001.…”
Section: Discussionmentioning
confidence: 99%
“…However, the molecular mechanisms involved in the transcriptional modulation of HDPs are not well-understood. The AP-1 transcription factor complex is the main transcription factor downstream of MAPK pathways and can bind with specific DNA sequences (45, 46). In the present study, the AP-1 subunits c-fos and c-jun were activated in IPEC-J2 cells incubated with L. plantarum ZLP001.…”
Section: Discussionmentioning
confidence: 99%
“…In the last years, numerous efforts were undertaken to demonstrate the health promoting activities of probiotics. Also, some of the mechanisms that leads to the protective functions of probiotics have been suggested (Priyamvada, 2016;Delcenserie, 2008;Yan, 2011). Studies in experimental animals and patients with intestinal inflammation disorders pointed out the potential application of probiotics such as Lactobacillus, Bifidobacteria as immunomodulatory agents (Dieleman, 2003;Gionchetti, 2000;Owczarek, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…It was demonstrated that two widely investigated Lactobacillus sp., L. plantarum and L. gasseri, have the ability to reciprocally modulate IL-10/IL-12 production in cell cultures (Sashihara, 2007). Also, the treatment of intestinal epithelial cells with Lactobacillus acidophillus resulted in the increase of the anti-inflammatory response in epithelial cells by the attenuation of NF-kBmediated inflammatory gene expression (Priyamvada, 2016). Some studies demonstrated that the use of probiotic mixtures might be more effective in reducing gastrointestinal disorders and inflammation than a single strain (Chapman, 2012;Taranu et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Studies with experimental animals and IBD patients pointed out the potential application of probiotics such as lactobacilli, bifidobacteria to prevent or treat colitis (24)(25)(26) . Data from in vitro studies showed that the treatment of intestinal epithelial cells with L. acidophilus resulted in induction of c-Fos and c-Jun proteins via extracellular signal-regulated kinase (Erk)1/2 activation (27) . In addition, probiotic bacteria could increase the antiinflammatory response in epithelial cells by shuttling the transcription factor NF-κB out of the nucleus, which resulted in the attenuation of NF-κB-mediated inflammatory gene expression (27,28) .…”
mentioning
confidence: 99%